Tolosa-Hunt Syndrome in Double-Hit Lymphoma - Prakash Peddi; Kevin M. Gallagher; Chandrikha Chandrasekharan; Qi Wang; Eduardo Gonzalez-Toledo; Binu S. Nair; Reinhold Munker; Glenn M. Mills; Nebu V. Koshy (Case Reports in Oncological Medicine)
Tolosa-Hunt syndrome (THS) is a painful condition characterized by hemicranial pain, retroorbital pain, loss of vision, oculomotor nerve paralysis, and sensory loss in distribution of ophthalmic and maxillary division of trigeminal nerve. Lymphomas rarely involve cavernous sinus and simulate Tolosa-Hunt syndrome. Here we present a first case of double-hit B cell lymphoma (DHL) relapsing and masquerading as Tolosa-Hunt syndrome. The neurological findings were explained by a lymphomatous infiltration of the right Gasserian ganglion which preceded systemic relapse. As part of this report, the diagnostic criteria for Tolosa-Hunt syndrome and double-hit lymphoma are reviewed and updated treatment recommendations are presented.